OPTIMIZATION OF CONTENT STRATEGY AND SOCIAL MEDIA ENGAGEMENT: A CASE STUDY OF KOPI JAGO ON INSTAGRAM - Sagala Pebri Antoni; Sumarwan Ujang; Yuliati Lilik Noor (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This study aims to analyze the content strategy and user engagement with the Instagram account of Kopi Jago, a mobile-based local coffee brand. Using content analysis, A/B testing, and sentiment analysis methods, this study evaluates 889 posts from 2019 to 2024. The results indicate that video content generates higher comments (69%) compared to photos, while shorter captions drive more likes. Neutral sentiment dominates (40%), with frequent complaints about stock availability and customer service. This research implies that a content strategy focused on video storytelling and improved customer service responses are key to building brand loyalty and a positive brand image.